Program Edukasi Melalui Media Meningkatkan Pengetahuan Ayah tentang 1000 Hari Pertama Kehidupan - Murtini, Mamik Sri; Astuti, KH Endah Widhi; Handajani, Sih Rini (Jurnal Empathy Pengabdian Kepada Masyarakat, 2023)
Background: The role of fathers is very important in supporting the First 1000 Days of Life (1000 HPK), but this group still lacks adequate education. The objective of this community service programme was to increase fathers' knowledge about the 1000 HPK through video-based education at PMB Mamik SM, Puhpelem Subdistrict, Wonogiri Regency. Methods: The community service programme included direct counselling and practical training on mask use, which was attended by 34 students from SD Negeri 4 Ngunut, Pacitan Regency. Evaluation was conducted through pre-tests and post-tests using valid and reliable questionnaires and observations during the activities. Results: There was a significant increase in fathers' knowledge about 1000 HPK after being given video education, with a higher average post-test score than the pre-test. Video education was effective in increasing fathers' understanding of the importance of their role in 1000 HPK to support optimal infant growth and development. Conclusion: This community service successfully increased fathers' awareness and readiness to support optimal child growth and development. The recommendation for this community service is to implement video-based education regularly and expand the target coverage to support the effective implementation of the stunting prevention acceleration programme.